Juridical review of tenant rent agreements in toll road rest area - Maskur, Muhammad Novrizal Firdaus; Wasitaatmadja, Fokky Fuad; Sadino, Sadino (Universitas Wiralodra, 2023)
Indonesia's economic growth is still centered on the island of Java, thus demanding the Government to conduct development outside Java. PT Hutama Karya (Persero) received a mandate from the Government to develop and build the Trans Sumatra Toll Road through Presidential Regulation No. 100/2014 was then amended through Presidential Regulation No. 117/2015. With the construction of toll roads on the island of Sumatra, economic growth there is hoped to increase. With the Trans Sumatra Toll Road, a rest area is needed to support road users when traveling. PT Hutama Karya entered into a lease agreement with tenants in the managed Toll Road rest area to rent out rental space in the rest area. This study aims to determine whether the laws and regulations regarding the PT Hutama Karya (Persero) OPT Division Rest Area Agreement have fulfilled the Legal Aspects of the Agreement and the Legal Aspects of Justice.